Continuity and change in family engagement in home learning activities across the early years - Hayes, Nicole (My University, 2015)
This research utilised data from The Longitudinal Study of Australian Children and explored continuity and change in parental engagement in home learning activities with young children. The findings indicated a decrease over time in parental engagement with children, from age to 2-3 years to 6-7 years. Rate of decrease impacted negatively on learning outcomes for language and literacy, and mathematical thinking, in the early years of school, when children were aged 6-7 years. Shared reading with children and interactions around everyday home activities and play, in which children and parents participate together, impact on children's later development.
Keywords: Children -- Early childhood; Families -- Parents and Parenting; Children -- Outcomes; Child Development -- Speech and Language; Child Development; Families and relationships; Childhood and child development; Child Development; Children; Families; Speech and Language; Parents and Parenting; Outcomes; Early childhood; Childhood and child development; Families and relationships